Pharmacological evaluation of Chloroxylonswietenia DC bark extract on alloxan induced Diabetic nephropathy in Wistar rats - Kaur, Manpreet; Sharma, Amit; Kaushik, Madan (Asian Journal of Pharmaceutical Research and Development, 2019)
Diabetes is now a days consider as common problem with serious issues. Diabetes cause various other dysfunctions and issues in various organs and parts of bodies, so it should be cured and treated. Chloroxylonswietenia DC bark extract proved to be helpful in treating diabetic problems. It is highly available and can cure various other problems caused by diabetes in bodies. In present study we have studied various properties, functions, effects, of extracts of Chloroxylonswietenia DC bark extracton alloxan induced Diabetic nephropathy in Wistar rats.